(untitled) (Journal of the College of Basic Education, 2022)
The ancient scholars of Arabic showed great care in the book of Sibawayh, and they were in it on three teams:.The first: She supported him and accepted him as a judge in all linguistic issues, which is the largest groupthe second :. I explained the book and its chapters, and tried to be fair in its criticism.Third: It was challenged and objections were recorded against it, which is the smallest difference.The research on the reasons for the appeal and objection to Sibawayh’s book ended with a number of reasons, the most important of which was the ambiguity of Sibawayh’s phrase, its brevity, the diversity of the chapters of the book in terms of grammar, morphology, sound, significance, the large number of scholars’ opinions that Sibawayh conveyed, and the lack of a clear methodology for the book, all of which made some scholars think that Sibawayh’s phrase was confused and wrong.